Philosophy of Patricia Benner, application in nursing training: Proposals of learning strategies - Escobar-Castellanos, Blanca (2019)
Changes in conceptions of providing and managing care have raised the need to modify nursing curricula to achieve significantly, the profile of the new nurse, and incorporate it into the workplace, with knowledge, skills and attitudes, that allow it to perform efficiently, with quality, greater scientific basis and modern management knowledge. The purpose is to propose learning strategies from the philosophical perspective of Patricia Benner that allow their development and contribute to the comprehensive education of the nursing student facilitating their transition from student to professional. The proposed learning strategies promote and encourage the development of skills by favoring the competence of the student, through the analysis, reasoning and argumentation of own phenomena of nursing, developing an autonomous and innovative clinical practice.